G-quadruplex-mediated reduction of a pathogenic mitochondrial heteroplasmy. (2nd May 2019) - Naeem, Mansur M; Maheshan, Rathena; Costford, Sheila R; Wahedi, Azizia; Trajkovski, Marko; Plavec, Janez; Yatsunyk, Liliya A; Ciesielski, Grzegorz L; Kaufman, Brett A; Sondheimer, Neal
Abstract: Disease-associated variants in mitochondrial DNA (mtDNA) are frequently heteroplasmic, a state of co-existence with the wild-type genome. Because heteroplasmy correlates with the severity and penetrance of disease, improvement in the ratio between these genomes in favor of the wild-type, known as heteroplasmy shifting, is potentially therapeutic. We evaluated known pathogenic mtDNA variants and identified those with the potential for allele-specific differences in the formation of non-Watson-Crick G-quadruplex (GQ) structures. We found that the Leigh syndrome (LS)-associated m.10191C variant promotes GQ formation within local sequence in vitro . Interaction of this sequence with a small molecule GQ-binding agent, berberine hydrochloride, further increased GQ stability. The GQ formed at m.10191C differentially impeded the processivity of the mitochondrial DNA polymerase gamma (Pol γ) in vitro, providing a potential means to favor replication of the wild-type allele. We tested the potential for shifting heteroplasmy through the cyclical application of two different mitochondria-targeted GQ binding compounds in primary fibroblasts from patients with m.10191T>C heteroplasmy. Treatment induced alternating mtDNA depletion and repopulation and was effective in shifting heteroplasmy towards the non-pathogenic allele. Similar treatment of pathogenic heteroplasmies that do not affect GQ formation did not induce heteroplasmy shift. Following treatment, heteroplasmic m.10191T>C cells had persistent improvements and heteroplasmy and a corresponding increase in maximal mitochondrial oxygen consumption. This study demonstrates the potential for using small-molecule GQ-binding agents to induce genetic and functional improvements in m.10191T>C heteroplasmy.